A Nursing Intelligence System to Support Secondary Use of Nursing Routine Data - Hackl, W.O.; Rauchegger, F.; Ammenwerth, E. (Applied Clinical Informatics, 2015)
Background: Nursing care is facing exponential growth of information from nursing documentation. This amount of electronically available data collected routinely opens up new opportunities for secondary use.Objectives: To present a case study of a nursing intelligence system for reusing routinely collected nursing documentation data for multiple purposes, including quality management of nursing care.Methods: The SPIRIT framework for systematically planning the reuse of clinical routine data was leveraged to design a nursing intelligence system which then was implemented using open source tools in a large university hospital group following the spiral model of software engineering.Results: The nursing intelligence system is in routine use now and updated regularly, and includes over 40 million data sets. It allows the outcome and quality analysis of data related to the nursing process.Conclusions: Following a systematic approach for planning and designing a solution for reusing routine care data appeared to be successful. The resulting nursing intelligence system is useful in practice now, but remains malleable for future changes.Citation: Hackl WO, Rauchegger F, Ammenwerth E A Nursing Intelligence System to Support Secondary Use of Nursing Routine Data. Appl Clin Inform 2015; 6: 418–428http://dx.doi.org/10.4338/ACI-2015-04-RA-0037
Keywords: Medical informatics; nursing informatics; databases; data integration; data mining